Analisis Pembagian Risiko dan Distribusi Keuntungan dalam Kontrak Pembiayaan Musyarakah - Narulita, Leira; Fauzatul Laily Nisa (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
Musyarakah financing is a partnership model where two or more parties combine capital to fund a project or business. This contract emphasizes fairness, transparency, and active participation. Islamic banks continue to develop musyarakah financing to meet customer needs, supported by supportive regulations. This research aims to understand the distribution of risks and profits in musyarakah financing and analyze its practices. Risks such as operational, market, and financial risks must be identified and managed properly. Profit-sharing is based on initial agreements that consider both capital and non-capital contributions. Evaluation of profit distribution practices highlights the importance of compliance with Sharia principles and transparency. Analysis of practitioner experiences reveals challenges such as differing perceptions and cash flow instability. Practical recommendations include improving risk management, transparency, and product innovation. Policy implications include strengthening regulations and incentives to support musyarakah financing. This research is expected to make a significant contribution to the development of Islamic financing in creating a fair, transparent, and sustainable business environment.